Change and Continuity in Indonesian Islamist Ideology and Terrorist Strategies - Fenton, Adam James (Al-Jamiah: Journal of Islamic Studies, 2014)
The âIslamisationâ of Indonesia has exerted a transformative force on every aspect of Indonesian society. That process continues today. It has created streams of change and continuity in thoughts, ideologies and practices, of enormous complexity. Strict doctrinal interpretation of Koranic text is not a new phenomenon, contrary to what some reports in the mass media might suggest. Its roots stretch back at least as far as the 1800s with the outbreak of violent conflicts between those urging a stricter, scripturalist application of Islam, and those adhering to traditionalist and colonialist ideologies --culminating in the Padri war of West Sumatra of 1821-38. Indicating an ostensible continuity of ideology, modern extremist ideologues, such as Abu Bakar Bashir, urge their followers toward violent conflict and terrorist actions based on an ideology of strict âMiddle Easternâ interpretation of fundamental Islamic tenets. This paper argues that the strategies of those carrying out radical and violent ideologies are undergoing change, as are the strategies of the authorities tasked with combating them. Radical groups have displayed a shift away from large-scale, attacks on symbolic foreign targets towards low-level violence primarily aimed at law enforcement authorities. Authorities, on the other hand, have shown a greater tendency to shoot dead those suspected of involvement with violent radical groups. This paper will examine the changing strategies of violent radical groups and the continuity, and evolution, of the underlying Islamic ideology that provides religious justification for their violent acts. The paper will argue that engaging Indonesiaâs politically active youth in an ideological dialogue on Islamism and democracy provides the best prospect for disengagement from, and breaking the cycle of recruitment for, radical violence and terrorism.[Proses panjang Islamisasi di Indonesia telah menghasilkan kekuatan transformatif di seluruh aspek kehidupan masyarakat Indonesia. Proses ini terus berlangsung hingga sekarang serta menciptakan gelombang perubahan berkesinambungan dalam pemikiran, ideologi, dan praktik-praktik dalam kompleksitas yang rumit. Penafsiran kaku atas ayat-ayat Quran sebenarnya bukanlah sesuatu yang baru, berbeda dengan apa yang selama ini diasumsikan di media. Fenomena seperti ini dapat dirunut kembali pada era 1800an, khususnya pada konflik bersenjata yang terjadi antara penganjur penerapan tekstual ajaran Islam dengan para penganut ideologi tradisional dan penjajah, yang berpuncak pada Perang Padri di Sumatra Barat tahun 1821-38. Dengan ideologi serupa, para ideolog modern dari kelompok garis keras, seperti Abu Bakar Bashir, mendorong pengikutnya untuk melakukan aksi kekerasan dan teror dengan mendasarkan diri pada ideologi ala Timur Tengah dengan penafsiran dasar-dasar Islam secara kaku. Tulisan ini mendalilkan bahwa strategi kelompok yang mengusung ideologi radikal dan kekerasan terus mengalami perubahan seiring perubahan strategi penguasa dalam menghadapi mereka. Strategi kelompok radikal telah berubah dari penyerangan berskala besar terhadap simbol-simbol asing bergeser pada kekerasan berskala kecil terutama pada persoalan penerapan hukum. Pemerintah, di sisi lain, cenderung mengambil tindakan tegas terhadap mereka yang diduga terlibat kekerasan kelompok radikal. Tulisan ini juga melihat perubahan-perubahan dan kesinambungan strategi dari kelompok radikal serta evolusi ideologi Islam yang menjustifikasi aksi-aksi kekerasan. Kesimpulan lainnya adalah bahwa keterlibatan kalangan muda dalam kegiatan dialog mengenai Islam dan demokrasi menjadikan mereka terhindar sekaligus memutus rantai rekrutmen gerakan radikal dan terorisme.]